Pi Chawa Performance in Muay Thai by Japanese People - Komkam, Pattara (Journal of Urban Culture Research, 2024)
This article examines the integration of Thai urban culture into Japan through the musical performance of the pi chawa, a traditional Thai oboe, in Muay Thai, a Thai martial art, by a Japanese woman. Data were collected from workshops in Osaka (2016) and Hokkaido (2017), supplemented by two years of follow-up training in Thailand. This cross-cultural exchange not only enhanced cultural awareness and appreciation but also fostered community bonds and provided educational opportunities. As a result, Yayoi Kuriyama emerged as a proficient Japanese female pi chawa musician, now performing in an all-female pi chawa klong khaek ensemble for Muay Thai matches in Japan. This integration highlights the broader benefits of cross-cultural learning in urban contexts, including economic boosts, social cohesion, and the preservation and innovation of cultural heritage.